Impact of Leadership Perception on Job Involvement, Organizational Politics and Commitment: An Empirical Evaluation in Banking Industry of Pakistan - Sarwar, Huma (Advances in Social Sciences Research Journal, 2017)
This study empirically examined a chain of workplace influences involving the influence of leadership on organizational politics and, in turn, the influence of organizational politics on job involvement and organizational commitment. The overarching question addressed by the study is to what extent, if any, do employees’ experiences of leadership affect their political perceptions and, in turn, to what extent do those political perceptions then influence employees’ involvement in their job and commitment to their organization. This was a study of patterns of organizational influences and how leaders shape organizational realities through their influence on employee perceptions of workplace politics. The concept of leadership examined in this study was obtained by tapping employees’ experience and perception of their supervisors and analyzing how that affects, in the first hypothesized causal link, the perceptions of organizational politics. The second hypothesized causal link was then expected to occur between the perception of politics influencing levels of job involvement and organizational commitment.